Reactions of 2-AMINO-6-METHYLPYRIMIDINONES-4 with ALKYL HALIDES C4-C9 - Kh. I. Nurbayev; N. À. Kuchkarov (European Science Publishing, 2024)
Alkylation of 2-amino-6-methylpyrimidine-4-one alkyl halides C4-C9 was performed. It is shown that, depending on the reaction conditions and the ratio of reagents, N3-alkylation products occur. It was found that, unlike methyl iodide, methyltosylate, alkylation of 2-amino-6-methylpirimidine-4-one alkyl halides C4-C9 in absolute alkoholproceeds with the formation of a mixture of isomeric N3-O4 alkyl products.
Keywords: 2-amino-6-methylpirimidin-4-one, C4-C9.